Kinerja Koperasi Peternak Sapi Bandung Utara Lembang, Jawa Barat - Hendrick Tio P. Tambunan; Nora H Pandjaitan; . Suryahadi (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2014)
At this moment, cooperative growth has experienced a very rapid development, which can be seen from the increasing number of diverse cooperative effort in Indonesia, especially in West Java. The ever-increasing needs of milk, added by milk production that has not met the needs of people in West Java makes a fierce competition among Cattle Ranchers Cooperative to produce milk. One of Cooperatives runs in this field is Cattle Ranchers Cooperative of North Bandung. The purpose of this study is (1) to analyze and evaluate management performance of KPSBU in West Java, (2) to analyze the level of liquidity, solvency, and profitability of KPSBU in West Java, (3) to develop business development strategy of KPSBU in West Java. The study used a descriptive survey approach, using primary and secondary data, as well as ratio analysis techniques (1) liquidity, (2) solvency, (3) profitability. Business development strategy will be prepared based on the analysis of the SWOT method and QSPM. Based on the analysis QSPM KPSBU has several strengths, weaknesses, opportunities, and threats. The most powerful force possessed KPSBU is quality fresh dairy products and its main drawback is the marketing of products less than the maximum, while the factors that affect the greatest opportunity is cooperation with local and international companies and the biggest threat is the bad weather which disrupted production and milk quality. Therefore, Cattle Ranchers Cooperative of North Bandung needs to make improvements on internal factors. It also reinforced by the value of the financial ratios of liquidity, solvency, and profitability that indicates that the company does not have a good value to pay a long-term and short-term debt as well as to generate profits in the company. Thus, Cattle Ranchers Cooperative of North Bandung must continue to strive to maintain and repair the service quality attribute and keeping customer satisfaction levels continue to rise.